2014
DOI: 10.1503/cjs.004513
|View full text |Cite
|
Sign up to set email alerts
|

“iBIM” — Internet-based interactive modules: an easy and interesting learning tool for general surgery residents

Abstract: Background:The increased use of information technology supports a resident-centred educational approach that promotes autonomy, flexibility and time management and helps residents to assess their competence, promoting self-awareness. We established a web-based e-learning tool to introduce general surgery residents to bariatric surgery and evaluate them to determine the most appropriate implementation strategy for Internetbased interactive modules (iBIM) in surgical teaching. Methods:Usernames and passwords wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…successfully implemented an internet-based knowledge module. 18 As the largest effect was found in a subgroup analysis of residents who completed a bariatric rotation before their study, it can be hypothesized that participating in surgeries and acquiring knowledge could best be combined. Next to knowledge gaining, preoperative ex vivo training was studied in several studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…successfully implemented an internet-based knowledge module. 18 As the largest effect was found in a subgroup analysis of residents who completed a bariatric rotation before their study, it can be hypothesized that participating in surgeries and acquiring knowledge could best be combined. Next to knowledge gaining, preoperative ex vivo training was studied in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Azer et al implemented an internet-based knowledge module on bariatric surgery to their general surgery curriculum. 18 The largest effect was found in a subgroup analysis of residents who completed a bariatric rotation before the study period. Zevin et al identified the available simulation-based training programs in addition to re-examining the learning curve of roux-y gastric bypass.…”
Section: Pre-operative Interventionsmentioning
confidence: 94%
See 1 more Smart Citation
“…In gynecology, a blended learning program using e-learning videos with face-to-face training modalities reduced the incidence of obstetric anal sphincter injuries [ 12 ]. Another study gave surgical residents access to internet-based interactive modules [ 13 ]. Residents had increased course score after completing the module and the tool was recommended by most who participated.…”
Section: Introductionmentioning
confidence: 99%
“…We know online learning opportunities offer learners control over how, when, and where they interact with learning materials, making it possible to determine the sequence and pace of one’s own learning [ 30 ]. Web-based learning can also facilitate self-assessment of competence [ 31 ]. For this reason, Web-based learning platforms have become commonplace in postgraduate education provision.…”
Section: Introductionmentioning
confidence: 99%